Index-based transmission for distributed generation in voltage stability and loss control incorporating optimization technique - Fareed Danial Ahmad Kahar; Ismail Musirin; Muhamad Faliq Mohamad Nazer; Shahrizal Jelani; Mohd Helmi Mansor (IAES International Journal of Artificial Intelligence (IJ-AI), 2020)
The integration of Distributed Generation (DG) in a distribution network may significantly affect distribution performance. With the penetration of DG, voltage security is no longer an issue in the transmission network. This paper presents a study of Distributed Generation on the IEEE 26-Bus Reliability Test System (RTS) with the use of Fast Voltage Stability Index (FVSI) for determining its location and incorporated with Grasshopper Optimization Algorithm (GOA) to optimize the sizing of the DG. The study emphasizes the power loss of the system in which a comparison between Evolutionary Programming (EP) and Grasshopper Optimization Algorithm is done to determine which optimization technique gives an optimal result for the DG solution. The results show that the proposed algorithm is able to provide a slightly better result compared to EP.